Dendritic cells in cord blood transplantation: a review - Pereira, MI (2011)
Dendritic cells (DCs) are a heterogeneous population of antigen-presenting cells derived from hematopoietic progenitors that bridge the transition between the innate and adaptive immune responses, while maintaining self-tolerance and Th1/Th2 homeostasis, by priming other cells in either an immunogenic or tolerogenic direction. Through their role in both innate and adaptive immunity, DCs play a major part in transplant engraftment and rejection and in graft-versus-host disease (GvHD). Preferentially tolerogenic or immunogenic DC subtypes offer targets for immunotherapy, to optimize transplant success rates and prolong disease-free and overall survival. Cord blood DCs are immature and preferentially tolerogenic, due to maternal-fetal tolerance, leading to better graft acceptance and immune reconstitution and explaining the lower incidence and severity of GvHD in CB transplantation, despite donor-host mismatching. Manipulation of DC maturation and cell loading with tumor-antigens can direct antitumor immunity and target minimal residual disease, as demonstrated for acute myeloid leukemia, optimizing the graft-versus-leukemia effect.